2010
DOI: 10.1063/1.3304896
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced ultraviolet electroluminescence from ZnO nanowires in TiO2/ZnO coaxial nanowires/poly(3,4-ethylenedioxythiophene)-poly(styrene-sulfonate) heterojunction

Abstract: The ultraviolet (UV) electroluminescence (EL) from the TiO2/ZnO coaxial nanowires (NWs)/poly(3,4-ethylenedioxythiophene)-poly(styrene-sulfonate) inorganic/organic heterostructure devices is greatly enhanced and the defect emission is significantly suppressed compared with the uncoated ZnO NW device at room temperature. The origins of the great changes in EL of ZnO NW devices are attributed to the surface modification of the sputtered TiO2 coating and the reduction in the pinhole traps on the surface of ZnO NWs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Subsequent pyrolysis converts the precursor to crystalline TiO 2 with concomitant removal of the polystyrene. The resulting TiO 2 seed pattern was then used to direct ZnO nanocrystals growth in a one-pot solution process [2,9,2627]. In addition, this type of laminated structure is considered advantageous in achieving the large aspect ratio necessary to observe the photonic bandgap via surface reflection measurements [9].…”
Section: Resultsmentioning
confidence: 99%
“…Subsequent pyrolysis converts the precursor to crystalline TiO 2 with concomitant removal of the polystyrene. The resulting TiO 2 seed pattern was then used to direct ZnO nanocrystals growth in a one-pot solution process [2,9,2627]. In addition, this type of laminated structure is considered advantageous in achieving the large aspect ratio necessary to observe the photonic bandgap via surface reflection measurements [9].…”
Section: Resultsmentioning
confidence: 99%
“…Experiments have also been carried out for the development of core-shell structure by coating on TiO 2 NPs with metal oxides such as Co 3 O 4 and ZnO. [68][69][70] Addition of oxygen-producing reaction catalysts such as Co 3 O 4 , enhances the photocurrent response of a DSSC under solar light. 68 Bilayers of metal-oxide semiconductors can increase the efficiency and reduce the recombination rate of a DSSC.…”
Section: Solar Cellsmentioning
confidence: 99%
“…Recent studies have suggested different approaches to improve (i) the chemical–physical properties of TiO 2 and (ii) its performances under visible light, such as doping with nitrogen (N) atoms and the formation of a heterojunction with other oxides, such as zinc oxide (ZnO). In fact, the presence of N dopants improves the TiO 2 absorption in the visible light , by forming band gap states that trap the photogenerated electrons, while the heterojunctions delay the rapid recombination holes–electrons. Therefore, the concerted use of heterojunctions and N-doping is, to date, the winning strategy to improve the photoactivity of the semiconductor systems. Previous experimental studies , have revealed that ZnO–TiO 2 heterojunctions reduce the electronic recombination since the TiO 2 and ZnO interfaces trap the photogenerated electrons and holes that are transferred to adsorbed species, initiating surface reduction/oxidation reactions. Therefore, the study of the structural and chemical–physical properties of the undoped and N-doped ZnO–TiO 2 heterojunction is fundamental to obtaining a semiconductor with improved photocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have suggested different approaches to improve (i) the chemical–physical properties of TiO 2 and (ii) its performances under visible light, such as doping with nitrogen (N) atoms 5 − 8 and the formation of a heterojunction with other oxides, 9 11 such as zinc oxide (ZnO). 12 14 In fact, the presence of N dopants improves the TiO 2 absorption in the visible light 15 , 16 by forming band gap states that trap the photogenerated electrons, while the heterojunctions delay the rapid recombination holes–electrons. Therefore, the concerted use of heterojunctions and N-doping is, to date, the winning strategy to improve the photoactivity of the semiconductor systems.…”
Section: Introductionmentioning
confidence: 99%